Diamond Fraud Detection in Property and Real Estate Companies - Cahyani, Nadhifa Risma; Aisyaturrahmi, Aisyaturrahmi (Jurnal Bisnis Mahasiswa, 2024)
The aim of this research is to detect fraud in property and real estate companies listed on the Indonesia Stock Exchange (BEI) in 2019-2022. The sample in this study used a purposive sampling method and obtained 24 property and real estate companies on the main board. The data collection method used is the library study and documentation method. The data analysis techniques used are descriptive statistical analysis, classical assumption testing, multiple linear regression analysis and model feasibility testing. The results of this research show that financial targets and changes in directors influence the occurrence of fraud in financial reports. Changing auditors and ineffective monitoring do not influence the occurrence of fraud in financial statements.